PENGARUH PELATIHAN PROFESI GURU TERHADAP PRESTASI KERJA GURU PADA SEKOLAH MENENGAH KEJURUAN 02 BATU - Unggul Bayu Aji (Universitas muhammadiyah malang, 2013)
Unggul Bayu AjiProgram Studi Manajemen FEB UMME-mail: unggulbayu@gmail.comABSTRACTThis watchfulness aim is that is: 1) to describe teacher profession training that carried out. 2) to describeteacher labour capacity level. 3) to analyze signifikansi teacher profession training variableinfluence towards teacher labour capacity. this watchfulness use is especially for school that is uponwhich input (input) to increase civil public servant labour capacity in teacher.Based on watchfulness result and discussion that done so can be pulled conclusion that teacherprofession training that carried out in country vocational high school 02 stones enters in goodcategory. teacher labour capacity in country vocational high school 02 Batu enters in tall categoryand influential teacher profession training significant towards teacher labour capacity in countryvocational high school 02 Batu.Suggestion that can be submitted in this watchfulness that is supposed school management sidealways cope to give input to training administrator side on the chance of matter that given cancorrectly as according to need level teachers perserta training. training matter that given genuinelycan to increase teacher ability at the area and education official or administrator institution alwayscope to maximise potential teachers passes training activity that is by using instructor genuinely hasability at the area each.Keywords: Training, Teacher Labour Capacity